Rethinking Solutions: Utilizing Islamic Ethics to Tackle Nigeria's Multifaceted Challenges - Olaitan Abdulkabir Oladapo (LECTURES: Journal of Islamic and Education Studies, 2023)
Nigeria, a country endowed with abundant natural resources, is plagued with multidimensional challenges that have hindered its progress and development. The challenges include poverty, corruption, insecurity, ethnic and religious conflicts, unemployment, poor infrastructure, and economic instability, among others. This study examines the potential of Islamic ethics as a solution to the multidimensional problems in Nigeria. Using a qualitative research approach, the study explores the ethical principles of Islam and how they can be applied in Nigeria to address the challenges facing the country. The findings of this study could contribute to the development of policies and strategies for sustainable development in Nigeria, providing a new perspective on how to address the challenges facing the country.